The Effect of Financial Literacy and Financial Security on the Ability to Pay Tuition Fees for Students of the Faculty of Economics and Business, University of August 17, 1945 Surabaya - Mustika Auliya Salma; Nanda Karisma Putri; Puri Handayani Sura Prewati (LPPM Institut Studi Islam Sunan Doe, 2024)
This research was conducted at the University of on August 17 1945 Surabaya, to determine the effect of financial literacy and financial resilience on the ability of students to pay tuition fees. Quantitative methodology was used in this study by distributing questionnaires to the parents of all FEB students at the University of on August 17 1945 Surabaya. A total of 117 respondents participated in this study. To test the hypothesis, the researcher runs the survey results through SPSS and uses the coefficient of determination (R2), f test, and t test. The results of these tests produce information on the impact of financial literacy and financial resilience on the ability to pay tuition fees for FEB students at the University of August 17 1945 Surabaya.